Covid-19 from the perspective of Islamic theology and spirituality - Ali, Mohammed Farid (2020)
We are not in the starting stage of Covid-19, but in the management stage. A pandemic like Covid-19 requires a holistic management approach. Prevention, treatment, social support and emotional management all have to come into play. The last three months of covid-19 saw scholars presenting verses of the Qur’an, Prophet’s hadiths, Islamic rulings, and moral teachings. All these deliberations provide an outline for the management of covid-19 from various perspectives. Are these deliberations in line with the Islamic Spirituality concept? This Webinar intends to answer this question.